Studies on Isolation and Characterization of Marine Actinomycete Strain NMR 2 from South East of India - K Nirmal Kumar, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Studies on Isolation and Characterization of Marine Actinomycete Strain NMR 2 from South East of India